2011
DOI: 10.1007/s10964-011-9636-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Predictors of Trajectories of Depressive Symptoms Among Adolescents from Immigrant Backgrounds

Abstract: Although there has been an increasing number of studies that has examined depression among adolescents from immigrant backgrounds, findings have been mixed, with some studies reporting that immigrant status is associated with risk, while others report that immigration status is linked to adequate or positive outcomes. Thus, it is important to explore how underlying predictors contribute to trajectories of depressive symptoms among adolescents from immigrant backgrounds. Using data from a nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
3
27
0
1
Order By: Relevance
“…Predicted associations found between decreased stress, increased parental, school, and peer support and decreased levels of depressive symptoms validate findings from the literature (Adkins et al, 2009;Coleman, 1998;Costello et al, 2008;Harker, 2001;Meadows, 2007;Mueller, 2009;H. Nguyen et al, 2011;Sabatier & Berry, 2008;Shen & Takeuchi, 2001;Van Voorhees et al, 2008;Walsh et al, 2010;Ying & Han, 2008).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Predicted associations found between decreased stress, increased parental, school, and peer support and decreased levels of depressive symptoms validate findings from the literature (Adkins et al, 2009;Coleman, 1998;Costello et al, 2008;Harker, 2001;Meadows, 2007;Mueller, 2009;H. Nguyen et al, 2011;Sabatier & Berry, 2008;Shen & Takeuchi, 2001;Van Voorhees et al, 2008;Walsh et al, 2010;Ying & Han, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Nguyen et al, 2011;Van Voorhees et al, 2008). Evidence indicates immigrant adolescents report less peer support than native adolescents, although it is unclear if this contributes to a detrimental effect on well-being (H. Nguyen et al, 2011;Oppedal & Røysamb, 2004). For example, although adolescent immigrants may be challenged to understand a new culture quickly, and in a way that fosters development of positive peer relations, they may also be from a collectivist culture that does not place the same importance on peer relations that is found in individualistic cultures (Gaudet et al, 2005;Oppedal & Røysamb, 2004;Rumbaut, 1994).…”
Section: Risk and Protective Factors Of Depressionmentioning
confidence: 99%
“…Perhaps the most relevant factor could be that internalizing problems, such as a depressed mood, depends on many more variables. Particularly in adolescence, peer environment and personal characteristics need to be considered (Nguyen et al 2011;Buck and Dix 2012). These factors may be an even more important influence than mother-adolescent agreement on adolescents' disclosure.…”
Section: Mother-adolescent Agreement and Psychosocial Outcomesmentioning
confidence: 99%
“…Strengths include: 1) healthy, intact families; 2) strong work ethic and aspirations; 3) community cohesion; 4) family beliefs that prioritize youth’s education (Fuligni, 1997; Fuligni & Hardway, 2004; Lese & Robbins, 1994). Studies of immigrant youth found protective factors for psychological wellbeing and substance use including: familism, family cohesion, fulfilling cultural expectations, having parental supervision, parent-child communication, lack of parent-child conflict, social support, and having a strong ethnic identity (Costigan, Koryzma, Hua, & Chance, 2010; Harker, 2001; Nguyen, Rawana, & Flora, 2011; Schwartz et al ., 2012; Smokowski, Chapman, & Bacallao, 2007; Torres Stone & Meyler 2007). Research demonstrates that immigrant youth, “have lower access to and make less use of high-quality institutions and programs that can facilitate their successful transition into adulthood” (Fuligni, 1998) and that this affects physical health, mental health, high-risk behaviors, educational and career outcomes.…”
Section: Introductionmentioning
confidence: 99%